2008
DOI: 10.1115/1.2836747
|View full text |Cite
|
Sign up to set email alerts
|

Combustion Performance of Liquid Biofuels in a Swirl-Stabilized Burner

Abstract: Fuels produced from renewable sources offer an economically viable pathway to curtail emissions of greenhouse gases. Two such liquid fuels in common usage are biodiesel and ethanol derived from soybean, corn, or other food crops. In recent years, significant effort has been devoted to identify alternate feedstock sources and conversion techniques to diversify the biofuels portfolio. In this study, we have measured emissions from flames of diesel, biodiesel, emulsified bio-oil, and diesel-biodiesel blends. Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…Hashimoto et al [4] reported lower NO x emissions of palm methyl esters compared to diesel fuel in a swirling flame established from a pressure atomizer. Sequera et al [5] studied the rate of pollutant emission of biofuel flames using an airblast-injector type axial swirl combustor, in which the emissions of diesel, soy methyl ester, soy ethyl ester and bio-oil pyrolised from hardwood were compared. Lower emissions of NO x and CO were obtained for biodiesel-blended fuels when compared at the same fuel mass flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…Hashimoto et al [4] reported lower NO x emissions of palm methyl esters compared to diesel fuel in a swirling flame established from a pressure atomizer. Sequera et al [5] studied the rate of pollutant emission of biofuel flames using an airblast-injector type axial swirl combustor, in which the emissions of diesel, soy methyl ester, soy ethyl ester and bio-oil pyrolised from hardwood were compared. Lower emissions of NO x and CO were obtained for biodiesel-blended fuels when compared at the same fuel mass flow rate.…”
Section: Introductionmentioning
confidence: 99%
“…Szybist et al [7] pointed out that compared to conventional diesel fuel (CDF) at high load, biodiesel blends generate 6%-9% higher NO x emissions. For gas turbine engines, Sequera et al [8] investigated the emissions of diesel and biodiesel using swirl burner gas turbine engines. Their results illustrated that biodiesel blended fuels emitted lower NO x and CO at constant fuel flow rates.…”
Section: Introductionmentioning
confidence: 99%
“…Sequera et al [8] investigated the emissions of diesel, soy methyl ester, soy ethyl ester and bio-oil pyrolised from hardwood. Their results demonstrated that biodiesel blended fuels emitted lower NOx and CO at conditions where the fuel flow rates are kept constant.…”
mentioning
confidence: 99%